Better off without the euro? Evaluating monetary policy and macroeconomic performance for the u.k. and sweden - Krause Montalbert, Stefan (2016)
I compare macroeconomic performance, measured by the volatility of real GDP and inflation, for two of the countries that opted not to enter the EMU: the United Kingdom and Sweden. In particular, I am interested in finding out how much of the macroeconomic performance changes experienced by the U.K. and Sweden after 1999 is due to increased efficiency in the conduct of independent monetary policy. Eventually, the objective is to analyze whether or not further changes in macroeconomic volatility could have been attained if these two countries would have instead adopted the Euro starting January 1999.